Mali Social Safety Nets - Cherrier, Cecile; Ninno, Carlo del; Razmara, Setareh (World Bank, Washington, DC, 2014)
This report shows that Mali s safety nets are insufficient to address the needs of the population and suggests ways to improve them. There is a need to devise a set of cost effective programs to expand the scope and coverage of the national safety net. Given that any reform plan must be financially feasible, the government must allocate its scarce resources to programs that are well targeted and efficient. Creating the fiscal room for safety nets will also depend on political will. The government needs to: (i) strengthen the strategic, institutional, and financial frameworks for designing, implementing, and monitoring and evaluating safety nets; and (ii) increase the effectiveness of the safety net system by strengthening existing programs and designing new ones.